2013
DOI: 10.1371/journal.pntd.0002357
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Versus Inapparent Outcome in Repeat Dengue Virus Infections Is Influenced by the Time Interval between Infections and Study Year

Abstract: Four dengue virus serotypes (DENV1-4) circulate globally, causing more human illness than any other arthropod-borne virus. Dengue can present as a range of clinical manifestations from undifferentiated fever to Dengue Fever to severe, life-threatening syndromes. However, most DENV infections are inapparent. Yet, little is known about determinants of inapparent versus symptomatic DENV infection outcome. Here, we analyzed over 2,000 DENV infections from 2004 to 2011 in a prospective pediatric cohort study in Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
232
4
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(248 citation statements)
references
References 34 publications
8
232
4
4
Order By: Relevance
“…It is important to point out that 2.5% (95% CI = 0.06-13.2) of the seroprevalence against DENV-4 was associated with a short-term multitypic neutralizing immune response, because the subjects were individuals recently infected by DENV who may not have been exposed to DENV-4 according to the viral surveillance of the region 6 ( Figure 2). However, viral surveillance in the studied area by local health authorities, although passive, is particularly robust compared with other areas within Mexico, but we cannot exclude the undetected circulation of any other serotype, which Montoya and others 14 reported previously. In the second age group (n = 27), a seroprevalence higher than 60% was observed, except for DENV-4 (42.9%, 95% CI = 24.5-62.8), whereas for the third age group (n = 70), the seroprevalence was higher than 65% for all four serotypes.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…It is important to point out that 2.5% (95% CI = 0.06-13.2) of the seroprevalence against DENV-4 was associated with a short-term multitypic neutralizing immune response, because the subjects were individuals recently infected by DENV who may not have been exposed to DENV-4 according to the viral surveillance of the region 6 ( Figure 2). However, viral surveillance in the studied area by local health authorities, although passive, is particularly robust compared with other areas within Mexico, but we cannot exclude the undetected circulation of any other serotype, which Montoya and others 14 reported previously. In the second age group (n = 27), a seroprevalence higher than 60% was observed, except for DENV-4 (42.9%, 95% CI = 24.5-62.8), whereas for the third age group (n = 70), the seroprevalence was higher than 65% for all four serotypes.…”
mentioning
confidence: 71%
“…Nevertheless, recent evidence shows that, in endemic communities, heterotypic secondary immune response is associated with low risk of clinical infection depending on the time that separates the first and the second infections. [13][14][15][16] Few studies of immunity against DENV have been carried out in Mexico. In Veracruz, the reported seroprevalence was 79.6%, similar to the seroprevalence reported in Matamoros.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 In a recent study, samples collected from a Sri Lankan pediatric dengue cohort (799 children) were used to investigate antibody responses in children with clinically unapparent and clinically apparent DENV infections. 19 It was reported that children with repeated unapparent infections had a greater number of broadly preexisting neutralizing antibodies against DENV serotypes than children with apparent infections.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] In the face of the increased risk of hospitalization due to cases of virologically confirmed dengue within the group of vaccinated children aged nine years or less, the follow-up periods after vaccination must be extended.…”
Section: Safety Of the Cyd-tdv Vaccinementioning
confidence: 99%